Hattie & Hudson - Van Dusen, Chris (Candlewick Press, 2017)
Exploring the lake near her home, young Hattie befriends a friendly but enormous lake monster she names Hudson who terrifies everyone else because of his size and they work together to teach her community about prejudging others by their appearance.